Análise dos resultados da produtividade e da percepção de gestores de micro e pequenas empresas participantes do programa agentes locais de inovação - LIMA, Jessica Alves Trindade (2022)
According to SEBRAE, Micro and Small Enterprises (MSEs) represent more than seven million formalized businesses and account for about 30% of the Gross Domestic Product (GDP), however these companies stand out for having low levels of productivity in relation to medium and large companies, and the difficulty of implementing innovations is one of the outstanding characteristics of this group. In this sense, the demonstration of the relationships between the efforts and the results of innovation actions aimed at small businesses are of relevant interest and can benefit small businesses themselves, the local agents that relate to them and government entities, like in Program “Agentes Locais de Inovação” (ALI). The study aimed to analyze how the contributions of innovation actions carried out under the ALI Program affect the productivity of participating micro and small companies. A qualitative, exploratory and descriptive methodological approach was adopted, using bibliographic and documentary research with the application of a five-point Likert scale, and characterized as a multiple case study. The main results obtained showed that participation in the ALI Program contributed to increasing the productivity of the group of companies analyzed, with the billing item being the one that most contributed to the improvement of results, and it can be affirmed that the managers perceived positively the actions of innovation promoted by the ALI program in the productivity of their companies.